Prisoners’ Rights: Access to Computers and the Internet - Geary , Jen; Zeleznikow , John (Journal of Law and Governance, 2015)
The purpose in this paper is to provide an overview about prisoners’ rights to utilize the Internet and security concerns that may arise with this. It is argued that prisoners should have limited access to the Internet, for such purposes as education, to maintain contact with their families, and to utilise information sources that may be located outside their institutions.